2014
DOI: 10.1007/s10955-014-1044-5
|View full text |Cite
|
Sign up to set email alerts
|

Near-Extreme Eigenvalues and the First Gap of Hermitian Random Matrices

Abstract: We study the phenomenon of "crowding" near the largest eigenvalue λ max of random N × N matrices belonging to the Gaussian Unitary Ensemble (GUE) of random matrix theory. We focus on two distinct quantities: (i) the density of states (DOS) near λ max , ρ DOS (r, N ), which is the average density of eigenvalues located at a distance r from λ max and (ii) the probability density function of the gap between the first two largest eigenvalues, p GAP (r, N ). In the edge scaling limit where r = O(N −1/6 ), which is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(82 citation statements)
references
References 58 publications
4
78
0
Order By: Relevance
“…the eigenvalues of the coupling matrix J that are close to λ max [8,17]. More precisely, we will see that the observables mentioned above (energy density, response and correlation functions) can be written in terms of the density of eigenvalues "seen" from λ max , the so called density of states (DOS) ρ DOS (r, N ) defined as [18,19] …”
Section: Summary Of Main Results Of the Papermentioning
confidence: 96%
See 3 more Smart Citations
“…the eigenvalues of the coupling matrix J that are close to λ max [8,17]. More precisely, we will see that the observables mentioned above (energy density, response and correlation functions) can be written in terms of the density of eigenvalues "seen" from λ max , the so called density of states (DOS) ρ DOS (r, N ) defined as [18,19] …”
Section: Summary Of Main Results Of the Papermentioning
confidence: 96%
“…The DOS (9) was recently studied in detail for matrices belonging to the Gaussian Unitary Ensemble (GUE, corresponding to the Dyson index β = 2) [19], using semiclassical orthogonal polynomials, as well as for more general Gaussian β-ensembles [20], using mainly scaling arguments. In particular, it was shown that the behavior of the average DOS ρ DOS (r, N ) exhibits two distinct behaviors depending on whether r ∼ O(1), or r ∼ O(N −2/3 ).…”
Section: Summary Of Main Results Of the Papermentioning
confidence: 99%
See 2 more Smart Citations
“…Details on the derivations, numerical checks and the outlook for future research will be provided elsewhere [36]. In the future, it will be interesting to study the order statistics for other ensembles and the crowding effects close to a specific eigenvalue in the bulk (see [50] for the first eigenvalue of GUE), as well as to investigate finite N corrections. In the Fermi gas picture (β = 2), our results provide the full statistics of particle number on a semi-infinite line (extending recent results [11,17,18]) and single-particle fluctuations in the bulk of a system of 1D fermions in a harmonic trap, including their LD tails.…”
mentioning
confidence: 99%